Seasonal Variation in Wastewater Quality of Mymensingh Municipality Area Discharged into the Brahmaputra River - Rahman, MS; Abedin, MZ; Rana, MM (Journal of Environmental Science and Natural Resources, 2015)
The present study was undertaken to monitor the seasonal variations in wastewater quality of Mymensingh municipality area discharged into different locations at the Brahmaputra River. Five sample collection points were purposively selected from five different discharge locations of the study area. The samples were collected during January to November 2012. Collected samples were analyzed for pH, Electrical Conductivity (EC), Total Dissolved Solids (TDS), Dissolved Oxygen (DO), Total Nitrogen and Available Phosphorus. The study results revealed that the value of EC, TDS, DO, Total Nitrogen and Available Phosphorus of the wastewater samples varied with seasons. The pH was consistently same through out the year, EC, TDS, Total Nitrogen and Available Phosphorus were relatively low in rainy season and high in winter, but DO was high in rainy season and low in winter. Considering the investigated parameters, the wastewater of Mymensingh municipality area that discharged into the Brahmaputra River was suitable for rice irrigation. For aquacultural purposes most of the discharge points of wastewater were not suitable except in rainy season, because the majority part of the year Dissolved Oxygen level was very low that may results in fish mortality. The wastewater containing excess phosphorus and nitrogen may cause algae growth in quantities sufficient to create bad odor. Dead and decaying of algae may also cause oxygen depletion which can kill fish and other aquatic organisms in the Brahmaputra River in winter season. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22098 J. Environ. Sci. & Natural Resources, 6(2): 65-69 2013